Physics Teacher's Misconceptions About Direct Current Material - Afifah Yuliani Adhim; Budi Jatmiko; Tjipto Prastowo (IJORER : International Journal of Recent Educational Research, 2021)
The teacher's conception is one of the misconceptions that students encounter, so it is critical to uncover the status of the teacher's conception in order to improve the students' conception. The purpose of this study is to identify physic’s teachers misconceptions about direct current material. There were 16 Physics Teachers in one of the districts in East Java, including 7 (seven) teachers from the Public High School (Negeri) and 9 (nine) teachers from private schools (Swasta). This research is a quantitative descriptive analysis research. A three-tier diagnostic test was used to analyze the data, which revealed that the average percentage of misconceptions faced by teachers was 58% in a medium category. The results also showed that physics teachers had the highest rate of misconceptions in the Potential Difference sub-concepts (94%), while the Series Circuit concept had the lowest proportion of misconceptions (25,50%). misconceptions experienced by physics teachers must be addressed immediately, because it will have an impact on students' conceptions. The results of this study are very important for policy makers, especially the Education Office to find solutions in breaking the chain of physics misconceptions